Role of ELT Textbooks in the Classroom: Hindrances or Facilitations - Saund, Ramesh (Exploration अन्वेषण, 2026)
This report is a result of a study concerned with the suitability and effectiveness of ELT textbooks for B.Ed students. The main objectives of this study were to explore the perceptions of B.Ed. First-year students towards the textbook and find out whether it scaffolds or diminishes creativity in students. This study is guided by a phenomenological research design under a qualitative method. I collected data through purposive sampling by conducting online interviews and recording participants’ responses. After that, I transcribed those responses into different sub-themes and analysed them along with specific themes. The present study revealed that using textbooks in the classroom enhances the students’ reading habits, along with their innovative ideas and knowledge, to address their decision-making abilities to enhance English language learning. The finding of the study also reveals that English textbooks help with planning instructions, providing mechanical knowledge, including pedagogical and content knowledge for English language learners.